ADHD as a Serious Risk Factor for Early Smoking and Nicotine Dependence in Adulthood. (April 2013) - Matthies, Swantje; Holzner, Sebastian; Feige, Bernd; Scheel, Corinna; Perlov, Evgeniy; Ebert, Dieter; Tebartz van Elst, Ludger; Philipsen, Alexandra
Objective: Tobacco smoking and ADHD frequently co-occur. So far, the bulk of research on the ADHD-smoking comorbidity has been done in children with ADHD and nonclinical adult samples. To assess smoking habits in adults with ADHD, the authors used the Fagerström Test for Nicotine Dependence (FTND).Method: In 60 adult outpatients, with an ADHD diagnosis according to Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV ) criteria and 60 age- and gender-matched controls, smoking habits were assessed with the FTND.Results: The authors replicated earlier findings in children confirming a higher rate of smokers in the ADHD group. The adult smokers with ADHD suffered from more severe nicotine dependence and smoked significantly more often when being sick. Females with ADHD smoked significantly more often and started smoking at an earlier age.Conclusion: Applying the FTND, the authors confirmed a high rate of highly dependent smokers among adult ADHD patients. The authors' findings point to a higher vulnerability for the development of nicotine dependence in women with ADHD.